The ETNA mission concept: Assessing the habitability of an active ocean world - Deutsch, Ariel N.; Panicucci, Paolo; Tenelanda-Osorio, Laura I.; Da Poian, Victoria; Cho, Yun H.; Venigalla, Chandrakanth; Mathanlal, Thasshwin; Castillo Specia, Emiliano; González Peytaví, Graciela; Guarriello, Andrea; Gunasekara, Onalli; Jones, Lewis; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Enceladus is an icy world with potentially habitable conditions, as suggested by the coincident presence of a subsurface ocean, an active energy source due to water-rock interactions, and the basic chemical ingredients necessary for terrestrial life. Among all ocean worlds in our solar system, Enceladus is the only active body that provides direct access to its ocean through the ongoing expulsion of subsurface material from erupting plumes. Here we present the Enceladus Touchdown aNalyzing Astrobiology (ETNA) mission, a concept designed during the 2019 Caltech Space Challenge. ETNA’s goals are to determine whether Enceladus provides habitable conditions and what (pre-)biotic signatures characterize Enceladus. ETNA would sample and analyze expelled plume materials at the South Polar Terrain (SPT) during plume fly-throughs and landed operations. An orbiter includes an ultraviolet imaging spectrometer, an optical camera, and radio science and a landed laboratory includes an ion microscope and mass spectrometer suite, temperature sensors, and an optical camera, plus three seismic geophones deployed during landing. The nominal mission timeline is 2 years in the Saturnian system and ~1 year in Enceladus orbit with landed operations. The detailed exploration of Enceladus’s plumes and SPT would achieve broad and transformational solar system science related to the building of habitable worlds and the presence of life elsewhere. The nature of such a mission is particularly timely and relevant given the recently released Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032, which includes a priority recommendation for the dedicated exploration of Enceladus and its habitable potential.